AN OVERVIEW OF ICT IN INDIAN AGRICULTURE - Joshi, Saurabh Arvind (2010)
A new paradigm of agricultural development is fast emerging. In developing and developed countries the overall development of agriculture is expanding in new directions. Information Communication Technology (ICT) plays a key role in improving the availability of agricultural production and market information in developing countries. Agriculture sector is the backbone of India's rural economy. With changing food consumption patterns, growth of organised food retailing, and favourable government policies, agriculture offers great potential in India. This report reviews the role of ICT in Indian agriculture, analyzes integration of supply chain management and ICT, understand recent trends and ICT initiatives, comprehend the barriers in ICT implementation, and discuss some ICT implementation techniques in present scenario.